Faktor Faktor yang Berhubungan dengan Pelaksanaan Teknik Menyusui dengan Benar pada Ibu Menyusui - Bara Miradwayana; Suryati Suryati; Fenti Hasnani (Jurnal Health Sains, 2021)
Breastfeeding is a complex baby behavior response that shows how babies get newborn food has a unique ability to move milk from the mother's breast. This study aims to find out what factors are related to the implementation of breastfeeding techniques correctly in nursing mothers in the target area of puskesmas pasar minggu subdistrict. This study uses cross sectional approach method. The implementation of breastfeeding techniques that are less correct occurred lower in 35.8% of respondents of mothers with normal childbirth compared to the incidence of breastfeeding techniques in respondents of mothers with caesarean delivery is higher at 43.5%. The implementation of improper breastfeeding techniques occurred in 44.7% of respondents who had no experience of exclusive breastfeeding compared to the incidence of improper implementation of breastfeeding techniques in respondents who had experience giving exclusive breast milk 31.6%. The implementation of incorrect breastfeeding techniques occurred in 57.1% of respondents who were not given health education about the correct breastfeeding techniques compared to the incidence of incorrect implementation of breastfeeding techniques in respondents who were given health education 27.1%.